PERAN RADIOGRAFER DALAM PEMERIKSAAN ULTRASONOGRAFI (USG) - Akhmadi; Rahayu Nia Pratiwi; Diah Rusita; Nurhasuna (Perhimpunan Radiografer Indonesia (PARI), 2021)
ABSTRACT Background: USG is one of the many areas of specialization for radiographers in Indonesia to develop their professional careers. Many countries in the world have implemented an ultrasound education system as an alternative field in the career development of health workers, in order to support the improvement of health facility services for the community. Especially in the Southeast Asia region, there has been special ultrasound education, namely in Malaysia, Singapore, and Thailand. In Indonesia, the USG education program has been specifically included in the radiographer education curriculum system, so that ultrasound is one part of the competence possessed by radiographers.Methods: This study uses a library research method or literature review, and a qualitative descriptive approach, through interviews, regarding the role of the radiographer in USGResults: Of the 3 (three) journals, literature reviews were conducted, sourced from Europe, especially England, and interviews were conducted with the researchers, then continued with 1 (one) interview from the United States sonographer, and 1 (one) interview from the Australian Sonologist. All of them explain the active role of the radiographer on ultrasound.Conclusions: Radiographers can play an active role in ultrasound services, especially in the field of ultrasound examination techniques, which will then produce a report in the form of an ultrasound image, and the results of an interim report, which will then be concluded by the doctor, in this particular case by the Radiology Specialist